1976
DOI: 10.1007/bf00219304
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for corticotropin releasing factor (CRF) synthesis in the preoptic nucleus of Xenopus laevis tadpoles

Abstract: For the study of the hypothalamo-hypophysial system of Xenopus laevis tadpoles, hypothalamic lesions were made by means of the electrocoagulation technique. Lesioning of the ventral region of the preoptic nucleus resulted in a decrease of the number of ACTH cells in the pars distalis of the pituitary gland and in a diminution of the PAS-positive reaction of these cells. In addition, regeneration of the neurosecretory cells of the ventral region of the preoptic nucleus observed 6 weeks after lesioning was accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Early studies in an amphibian ( Bufo melanosticus ) found an elevation in plasma corticosteroids after electrical stimulation of the POA, ventral hypothalamus, or the median eminence, but not after stimulation of other brain regions (52). Furthermore, lesioning of the ventral region of the POA in X. laevis tadpoles caused the pituitary corticotropes to regress (53). In the present study, we investigated the effects of a physical stressor, handling/shaking on CRH neuronal physiology in X. laevis .…”
Section: Discussionmentioning
confidence: 99%
“…Early studies in an amphibian ( Bufo melanosticus ) found an elevation in plasma corticosteroids after electrical stimulation of the POA, ventral hypothalamus, or the median eminence, but not after stimulation of other brain regions (52). Furthermore, lesioning of the ventral region of the POA in X. laevis tadpoles caused the pituitary corticotropes to regress (53). In the present study, we investigated the effects of a physical stressor, handling/shaking on CRH neuronal physiology in X. laevis .…”
Section: Discussionmentioning
confidence: 99%
“…The distribution and development of hypothalamic neuroendocrine cells and fibers is well documented in mammals (Ugrumov, 1991). In amphibians, however, there have been few reports on the development of the 0 1995 WILEY-LISS, INC. hypothalamus (Carr and Norris, 1990;Notenboom et al, 1976). In addition, almost no studies have been attempted to investigate the correlational development of the hypothalamo-adenohypophysial and hypothalamo-neurohypophysial systems in species higher than amphibians.…”
Section: Hypothalamus Immunohistochemistry Xenopus Zaeuismentioning
confidence: 99%